Mango phenolics increase serum apolipoprotein A1/B ratio in rats fed high cholesterol and sodium cholate diets - Domínguez Avila, J. Abraham (2018)
ABSTRACT: BACKGROUND: Serum lipoproteins are in dynamic equilibrium, partially controlled by the apolipoprotein A1 to apolipoprotein B ratio (APOA1/APOB). Freeze-dried mango pulp (FDM) is a rich source of phenolic compounds (MP) and dietary fiber (MF), although their effects on lipoprotein metabolism have not yet been studied. RESULTS: Thirty male Wistar rats were fed with four different isocaloric diets (3.4 kcal g−1) for 12weeks: control diet, high cholesterol (8 g kg−1) + sodium cholate (2 g kg−1) diet either alone or supplemented with MF (60 g kg−1), MP (1 g kg−1) or FDM (50 g kg−1). MP and FDMreduced food intake,whereas MF andMP tended to increase serum APOA1/APOB ratio, independently of their hepatic gene expression. This suggests that lipoprotein metabolismwas favorably altered by mango bioactives,MP also mitigated the non-alcoholic steatohepatitis that resulted fromthe intake of this diet. CONCLUSION: We propose that phenolics are the most bioactive components of mango pulp, acting as anti-atherogenic and hepatoprotective agents, with a mechanism of action tentatively based on changes to the main protein components of lipoproteins.